Analisis Pengaruh Efisiensi Modal Kerja, Likuiditas Dan Leverage Terhadap Profitabilitas (Studi Kasus Pada Perusahaan Manufaktur Di Bursa Efek Indonesia Tahun 2013-2015) - Lestari, Febry Ayu; , Drs. Ma'ruf, MM (2017)
The purpose of this study was to test the effect of the efficiency of working capital, liquidity, and leverage on profitability in a manufacturing company. The population in this study are all manufacturing companies listed in Indonesia Stock Exchange period 2013 to 2015 as many as 128 companies, while the sample selection is done by using purposive sampling method were selected based on several criteria in order to obtain a sample of 28 companies. The results of the analysis obtained value coefficient determination R square of 0.344 or 34.4%. This shows all the independent variables have an impact of 34.4% on the dependent variable, while the remaining 65.6% is influenced by other variables. At t test found that the variable efficiency of working capital has no effect on profitability, while liquidity and leverage variable has an effect on profitability. F- test analysis results obtained value Fcount > Ftable (13.102 > 2.76). Means together variable working capital efficiency, liquidity, and leverage significant effect on profitability.